Gut Microbes in Gynecologic Cancers: Causes or Biomarkers and Therapeutic Potential - Han, Mengzhen; Wang, Na; Han, Wenjie; Ban, Meng; Sun, Tao; Xu, Junnan (Frontiers in Oncology, 2022)
The human intestine is home to a variety of microorganisms. In healthy populations, the intestinal flora shares a degree of similarity and stability, and they have a role in the metabolism, immunological response, and physiological function of key organs. With the rapid advent of high-throughput sequencing in recent years, several researchers have found that dysbiosis and the composition changes of the human gut microflora potentially cause physical problems and gynecological malignancies among postmenopausal women. Besides, dysbiosis hinders tumor treatment. Nonetheless, the importance of maintaining homeostatic gut microbiota and the effective use of probiotics in the treatment of gynecological malignancies should not be disregarded. Moreover, intestinal flora regulation and the involvement of probiotics as well as associated biologically active substances in gynecological malignancies could be an adjuvant treatment modality related to surgery and chemoradiotherapy in the future. Herein, this article aims to review the potential relationship between gut microorganisms and postmenopausal status as well as gynecologic malignancies; then the relationship between gut microbes and early screening as well as therapeutic aspects. Also, we describe the role of probiotics in the prevention, treatment, and prognosis of gynecologic malignancies.